Mechanistic study on electroacupuncture-regulated circadian autophagy for inhibiting ferroptosis in hippocampal neurons and alleviating depression-like behaviors in adulthood induced by early chronic sleep deprivation - Wu, Yuzhu; Chen, Xinwang; Liu, Feixiang; Feng, Yanchen; Liao, Ziyun; Bu, Xinyu; Fu, Wen; Gao, Jing; Wu, Lihua; Fan, Linyuan; Yang, Qian; Yue, Penglin; et al. (Frontiers in Neurology, 2025)
Early-life chronic sleep deprivation (CSD) represents a significant risk factor for the development of adult depressive-like behaviors, although the precise molecular mechanisms underlying this association remain incompletely elucidated. In this study, we established a CSD rat model using a rodent sleep deprivation apparatus and employed behavioral tests to assess the effects of early electroacupuncture intervention on adult depressive-like behaviors. The underlying molecular mechanisms were systematically investigated through integrated experimental approaches including Prussian blue staining, transmission electron microscopy, enzyme-linked immunosorbent assay, and Western blot analysis. The experimental results demonstrated that the CSD group rats exhibited significant depressive-like behaviors, accompanied by pathological alterations such as increased iron deposition in hippocampal tissues and structural damage to neuronal mitochondria. Electroacupuncture intervention facilitated hippocampal neuronal repair and remodeling through multiple mechanisms, including the regulation of iron metabolism homeostasis, enhancement of antioxidant capacity, inhibition of ferroptosis, and suppression of excessive autophagy, thereby reversing the CSD-induced depressive-like behaviors. This study provides novel therapeutic strategies and mechanistic insights for the prevention and treatment of adult-onset depression induced by early-life chronic sleep deprivation.